Pandemic H1N1 influenza in Brazil: analysis of the first 34,506 notified cases of influenza-like illness with severe acute respiratory infection (SARI) - Oliveira, Wanderson Kleber de (2009)
Gerson Oliveira Penna - Fundação Oswaldo Cruz. Fiocruz Brasília. Brasília, DF, Brasil. Documento produzido em parceria ou por autor vinculado à Fiocruz, mas não consta à informação no documento do vinculo com a unidade da Fiocruz Brasília.